APPLICATION OF NEW APPROACHES TO ENSURE THE EFFICACY OF CORPORATE MANAGEMENT IN BANKS (World Bulletin of Management and Law, 2023)
The essential component of creating a safe and healthy bank is board and management monitoring. In other words, director oversight is the key force that keeps a bank on track, and it is a vital component of a bank's success. The Federal Reserve and other banking authorities have long recognized the value of independent directors and constructive board engagement. Many supervision policies and examination guidelines used by federal banking examiners reflect this. This article discusses the areas that are especially crucial to the bank's successful performance
Keywords: Corporate management; four Ps of corporate governance; successful corporate governance